If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 3x + -2 Reorder the terms: 9x = -2 + 3x Solving 9x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9x + -3x = -2 + 3x + -3x Combine like terms: 9x + -3x = 6x 6x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 6x = -2 + 0 6x = -2 Divide each side by '6'. x = -0.3333333333 Simplifying x = -0.3333333333
| 18p+11q+p-4q-3p= | | -2x-3=4x+2 | | 2x+(3x/4)=11 | | 2X+2X=68 | | myles=lie | | 4(x^2+6)=168 | | 10y^7+35y^6+25y^5= | | 9-5y=37+2y | | 2x^2=-4+6x | | 500=6x^3+5x^2 | | 2x^2=-4+6 | | 10x+8=4x+25 | | 12m+4n-6m+9n= | | Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) | | y=8(8)+7 | | 0.36=x/x | | 10pr+8p-5sr-4s= | | 1+2(3x-4)=3(5-x)-4 | | 2x^2-15x+7/6x^2-3x | | (275)(38/55)(11/25) |